Site specific mutation of the Zic2 locus by microinjection of TALEN mRNA in mouse CD1, C3H and C57BL/6J oocytes - Davies, B; Davies, G; Preece, C; Puliyadi, R; Szumska, D; Bhattacharya, S (Public Library of Science, 2013)
Transcription Activator-Like Effector Nucleases (TALENs) consist of a nuclease domain fused to a DNA binding domain which is engineered to bind to any genomic sequence. These chimeric enzymes can be used to introduce a double strand break at a specific genomic site which then can become the substrate for error-prone non-homologous end joining (NHEJ), generating mutations at the site of cleavage. In this report we investigate the feasibility of achieving targeted mutagenesis by microinjection of TALEN mRNA within the mouse oocyte. We achieved high rates of mutagenesis of the mouse Zic2 gene in all backgrounds examined including outbred CD1 and inbred C3H and C57BL/6J. Founder mutant Zic2 mice (eight independent alleles, with frameshift and deletion mutations) were created in C3H and C57BL/6J backgrounds. These mice transmitted the mutant alleles to the progeny with 100% efficiency, allowing the creation of inbred lines. Mutant mice display a curly tail phenotype consistent with Zic2 loss-of-function. The efficiency of site-specific germline mutation in the mouse confirm TALEN mediated mutagenesis in the oocyte to be a viable alternative to conventional gene targeting in embryonic stem cells where simple loss-of-function alleles are required. This technology enables allelic series of mutations to be generated quickly and efficiently in diverse genetic backgrounds and will be a valuable approach to rapidly create mutations in mice already bearing one or more mutant alleles at other genetic loci without the need for lengthy backcrossing.